2012
DOI: 10.1016/j.ceb.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Inside-out, outside-in, and inside–outside-in: G protein signaling in integrin-mediated cell adhesion, spreading, and retraction

Abstract: The integrin family of cell adhesion receptors mediates bi-directional signaling: “inside-out” signaling activates the ligand binding function of integrins and “outside-in” signaling mediates cellular responses induced by ligand binding to integrins leading to cell spreading, retraction, migration, and proliferation. Integrin signaling requires both heterotrimeric G proteins and monomeric small G proteins. This review focuses on recent development in the roles of G proteins in integrin outside-in signaling. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
173
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 66 publications
1
173
1
Order By: Relevance
“…These findings are consistent with the notion that distinct RGD-containing ␣v␤3 ligands may promote different biological responses. Signaling downstream from ␣v␤3 is complex, and studies have indicated that simple binding of ␤3-integrin does not necessarily lead to productive outside-in integrin signaling (63). In fact, the capacity of ␤3-integrins to promote outside-in signaling depends on multiple factors, including the extent of receptor clustering and subsequent generation of mechanical tension within the actin cytoskeleton, recruitment of adaptor and accessory proteins such as G␣13 and Kindlin-2, and the association of the integrin with protein-tyrosine phosphatases and certain growth factor receptors (64 -67).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the notion that distinct RGD-containing ␣v␤3 ligands may promote different biological responses. Signaling downstream from ␣v␤3 is complex, and studies have indicated that simple binding of ␤3-integrin does not necessarily lead to productive outside-in integrin signaling (63). In fact, the capacity of ␤3-integrins to promote outside-in signaling depends on multiple factors, including the extent of receptor clustering and subsequent generation of mechanical tension within the actin cytoskeleton, recruitment of adaptor and accessory proteins such as G␣13 and Kindlin-2, and the association of the integrin with protein-tyrosine phosphatases and certain growth factor receptors (64 -67).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The conformational changes can be caused by Òinside-outÓ signaling, during which proteins within the cell, such as talin and kindlins, bind to the transmembrane base of the β domain and induce the change in conformation outside the cell by disrupting the salt bridge. 1,[11][12][13] Alternatively, Òoutside-inÓ signaling can also result in conformational changes when the integrin ectodomain interacts with a ligand, allowing the cell to sense and react to the extracellular environment. 12,16 and Tyr122 of the β 3 subdomain may be central to interacting with the inactive integrin without inducing any conformational changes in the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…1,[11][12][13] Alternatively, Òoutside-inÓ signaling can also result in conformational changes when the integrin ectodomain interacts with a ligand, allowing the cell to sense and react to the extracellular environment. 12,16 and Tyr122 of the β 3 subdomain may be central to interacting with the inactive integrin without inducing any conformational changes in the receptor. 16 The inhibition of integrins can be achieved by preventing the activation of the receptor or by blocking the binding site, with the latter being the more common approach.…”
Section: Introductionmentioning
confidence: 99%
“…G protein-dependent and G protein-independent pathways each have the capacity to initiate numerous intracellular signaling cascades to mediate these effects [4]. G proteins are GTPases (guanosine triphosphatases) that cycle between a GDP-bound form and a GTP-bound form [5]. The GTP-bound G protein is an active form that interacts with downstream effectors and transmits signals, during which the bound GTP is often hydrolyzed to GDP and the G protein recycles into the inactive GDP-bound form [5].…”
Section: Introductionmentioning
confidence: 99%